The dual-design-based pneumatic simulator as supporting media for electro-pneumatic practicum in vocational higher education - Sulaeman Deni Ramdani; Angga Pangestu; Haris Abizar (Jurnal Pendidikan Vokasi, 2019)
This study aims to: (1) determine the process of developing a learning media simulator for electro-pneumatic systems based on dual design, (2) knowing the effectiveness of learning media in the form of electro-pneumatic system simulators based on dual design. This research is a research and development adapted from the 4D development model, namely, Define, Design, Develop, and Disseminate. The subjects of this study were students of Mechanical Engineering Education in Semester IV and V, with 30 students taking pneumatic hydraulic courses. Data collection techniques in this study used questionnaires and interviews with research instruments in the form of interview guidelines and questionnaires. The data obtained were analyzed with a descriptive quantitative method. The results show that (1) the results of the development of learning media for electro-pneumatic system simulators based on Dual Design as supporting media for electro-pneumatic practices produce three main components, namely the working system in the pneumatic electro system, wiring diagrams, and electrical circuits, (2) the feasibility results of expert validation media is 84% (Very Good), expert material validation is 92% (Very Good), and user validation is 86% (Very Good). Therefore, the learning media for electro-pneumatic system simulator is feasible as a learning media in pneumatic hydraulic courses.